A commentary on interpreting the United States preventive services task force autism screening recommendation statement. (February 2021) - Hickey, Emily; Sheldrick, R Christopher; Kuhn, Jocelyn; Broder-Fingert, Sarabeth
In 2016, the US Preventive Services Task Force concluded that there was "insufficient" ("I" statement) evidence to support universal primary care screening for autism spectrum disorder. The statement led to controversy among research and clinical communities. Although a number of papers have since been published arguing for the potential benefit of autism spectrum disorder screening, none adequately address the potential harms of autism spectrum disorder screening. This evidence gap may relate to confusion regarding how the US Preventive Services Task Force conceptualizes and evaluates potential harm. In this commentary, we explore how the US Preventive Services Task Force operationalizes harm and discuss how the potential for harm was described in the "I" statement on autism spectrum disorder screening. This information can serve as a guide for investigators working to study the benefits and harms of autism spectrum disorder screening in order to fill the research gaps cited by the US Preventive Services Task Force report. Finally, we recommend future research directions for exploring harms of autism spectrum disorder screening, filling cited research gaps, and ultimately ensuring that the benefits of autism spectrum disorder screening truly outweigh the harms for all children and their families.